UICC manual of clinical oncology - O'Sullivan, Brian, 1952-; Brierley, James; International Union against Cancer (Chichester, West Sussex, UK ; Hoboken, NJ : John Wiley and Sons, Ltd., 2015)
'Provides a concise, accessible and feasible reference to state of art multidisciplinary clinical oncology'--Provided by publisher.
Curative surgical therapy and treatment sequencingNon-curative surgery for cancer; Surgical complications; Quality of surgical care; Postoperative surveillance; New technologies; Recommended reading; Chapter 10: Principles of radiotherapy; Introduction: Radiation oncology and radiation biology in the global picture of oncology; Biological basis of radiation oncology; General principles of radiation oncology; Recommended reading; Chapter 11: Principles of systemic therapy; Types of anticancer drugs; Strategies of systemic cancer treatment
Preceeded by UICC manual of clinical oncology / editor, Raphael E. Pollock. 8th ed. 2004.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Cancer -- Handbooks, manuals, etc; Neoplasms; Electronic books; Handbooks and manuals; Handbooks